The Use of Biochard for Improving Soil Quality and Environmental Services - Kusman, Hardi; Mulyati, Mulyati; Suwardji, Suwardji (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Biochar is recognized as a versatile and sustainable tool for improving agricultural and environmental conditions due to its unique physicochemical properties, such as soil fertility, nutrient retention and water holding capacity. The presence of biochar, which contains stabilized carbon, not only has a positive impact on plant growth and crop yields through microbial activity, but can also act as a sorbent to remove contaminants from soil and water. However, the use of biochar in soil and its effects on ecosystem services depend on several factors. This article explores the impact of biochar use on soil and the potential to address ecosystem service challenges by improving soil composition, increasing access to water, and removing contaminants, all to promote sustainable agriculture. The method of this article consists of a literature review by collecting data from various sources such as scientific journals, books and seminar proceedings. The data obtained were qualitatively analyzed to review and identify the information, resulting in a critical and comprehensive explanation and discussion of the role of biochar in improving soil and environmental quality for environmental services. The results of the literature review are presented in the form of a coherent, systematic and critical narrative. The results of this article review indicate that on-farm biochar application contributes significantly to climate change mitigation through various mechanisms, including biochar's ability to sequester carbon, improve soil quality, and minimize greenhouse gas emissions.